Dietary recommendations for Ethiopians on the basis of priority diet-related diseases and causes of death in Ethiopia: An umbrella review - Bekele, Tesfaye Hailu; Trijsburg, Laura; Brouwer, Inge D.; Vries, Jeanne H.M. de; Covic, Namukolo M.; Kennedy, Gina; Alemayehu, Dawit; Feskens, Edith J.M. (Elsevier, 2023)
Food-based dietary guidelines (FBDG) need to be evidence-based. As part of the development of Ethiopian FBDG, we conducted an umbrella review to develop dietary recommendations. Protein-energy malnutrition (PEM), deficiencies of vitamin A, zinc, calcium, or folate, cardiovascular diseases (CVD), and type 2 diabetes mellitus (T2DM) were selected as a priority. Systematic reviews were eligible if they investigated the impact of foods, food groups, diet, or dietary patterns on priority diseases. After a search, 1513 articles were identified in PubMed, Scopus, and Google Scholar published from January 2014 to December 2021. The results showed that 19 out of 164 systematic reviews reported the impact of diet on PEM or micronutrient deficiencies. Daily 30–90 g whole-grain consumption reduces risk of CVD and T2DM. Pulses improve protein status, and consuming 50–150 g/d is associated with a reduced incidence of CVD and T2DM. Nuts are a good source of minerals, and consuming 15–35 g/d improves antioxidant status and is inversely associated with CVD risk. A daily intake of 200–300 mL of milk and dairy foods is a good source of calcium and contributes to bone mineral density. Limiting processed meat intake to <50 g/d reduces CVD risk. Fruits and vegetables are good sources of vitamins A and C. CVD and T2DM risks are reduced by consuming 200–300 g of vegetables plus fruits daily. Daily sugar consumption should be below 10% of total energy to lower risk of obesity, CVD, and T2DM. Plant-based fat has favorable nutrient profiles and modest saturated fat content. The association of saturated fatty acids with CVD and T2DM is inconclusive, but intake should be limited because of the low-density lipoprotein cholesterol-raising effect. Plant-based diets lower risk of CVD and T2DM but reduce micronutrient bioavailability. The review concludes with 9 key dietary recommendations proposed to be implemented in the Ethiopian FBDG. This review was registered at PROSPERO (CRD42019125490).